TRANSPARENCY OF BPI DANANTARA IN MANAGING THE DIVIDENDS OF STATE-OWNED ENTERPRISES - Zita Humairoh; Reka Dewantara; Amelia Sri Kusuma Dewi (PT. Radja Intercontinental Publishing, 2026)
The transformation of Indonesian State-Owned Enterprises (SOEs) through the establishment of the Danantara Investment Management Agency (BPI Danantara) marks a paradigm shift toward a Sovereign Wealth Fund (SWF) model. This research aims to analyze the transparency mechanisms of dividend management under the framework of Law No. 16 of 2025 concerning SOEs, specifically in mitigating the risk of